Long-Term Sustainability and Acceptance of Antimicrobial Stewardship in Intensive Care: A Retrospective Cohort Study*. Issue 1 (January 2021) - Sehgal, Prateek; Elligsen, Marion; Lo, Jennifer; Lam, Philip W.; Leis, Jerome A.; Fowler, Rob; Pinto, Ruxandra; Daneman, Nick
Abstract : OBJECTIVES: To evaluate long-term uptake of an antimicrobial stewardship audit-and-feedback program along with potential predictors of stewardship suggestions and acceptance across a diverse ICU population. DESIGN: A retrospective cohort study. SETTING: An urban, academic medical institution. PATIENTS: Patients admitted to an ICU who received an antimicrobial stewardship program suggestion between June 2010 and September 2019. INTERVENTION: None. MEASUREMENTS AND MAIN RESULTS: The antimicrobial stewardship program provided 7, 749 antibiotic assessments over the study period and made a suggestion to alter therapy in 2, 826 (36%). Factors associated with a higher likelihood of receiving a suggestion to alter therapy included shorter hospital length of stay prior to antimicrobial stewardship program review (odds ratio 1.15 for ⩽ 5 d; 95% CI 1.00–1.32), admission to cardiovascular (1.37; 1.06–1.76) or burn surgery (1.88; 1.50–2.36) versus general medicine, and preceding duration of antibiotic use greater than 5 days (1.33; 1.10–1.60). Assessment of aminoglycosides (2.91; 1.85–4.89), carbapenems (1.93; 1.54–2.41), and vancomycin (2.71; 2.19–3.36) versus ceftriaxone was more likely to result in suggestions to alter therapy. The suggestion acceptance rate was 67% (1, 895/2, 826), which was stable throughout the study period. Admission to a level 3 ICU was associated with higher likelihood of acceptance of suggestions (1.50; 1.14–1.97). Factors associated with lower acceptance rates were admission to burn surgery (0.64; 0.45–0.91), treatment of pneumonia (0.64; 0.42–0.97 for community-acquired and 0.65; 0.44–0.94 for ventilator-acquired), unknown source of infection (0.66; 0.48–0.92), and suggestion types of "narrow spectrum" (0.65; 0.45–0.94), "change formulation of antibiotic" (0.42; 0.27–0.64), or "change agent of therapy" (0.63; 0.40–0.97) versus "change of dose". CONCLUSIONS: An antimicrobial stewardship program implemented over a decade resulted in sustained suggestion and acceptance rates. These findings support the need for a persistent presence of audit-and-feedback over time with more frequent suggestions to alter potentially nephrotoxic agents, increased efforts toward specialized care units, and further work approaching infectious sources that are typically treated without pathogen confirmation and identification. Abstract : Supplemental Digital Content is available in the text.